Zinner syndrome mimicking bladder outlet obstruction managed with aspiration - Kori, Ronal (Urol Ann, 2019)
Zinner syndrome is a rare cystic malformation of seminal vesicle which consists a triad of unilateral renal agenesis, ipsilateral seminal vesicle cyst, and ejaculatory duct obstruction. The usual presentation is between the third and fourth decades of life, with infertility being the most common complaint. Ultrasound, cystoscopy, and magnetic resonance tomography (MRI) can easily detect this condition. Treatment option varies according to the presenting symptoms of the patient. We present a case of a 19-year-old male with recurrent episodes of urinary tract infection (UTI) and poor urinary stream. On ultrasound examination, the patient was found to have absent right kidney with a cystic swelling noted to be arising from prostate or seminal vesicle region which was further confirmed on MRI examination. Cystoscopy reveals a bulge on the right side of the verumontanum abutting the neck of the bladder. An ultrasound-guided aspiration of the cyst was performed which relieved the symptoms of the patient. Cystic abnormalities of the seminal vesicle are very uncommon. Symptomatic cases may present as recurrent UTI, infertility, bladder outlet obstruction, and painful ejaculation. Surveillance may be the option in the absence of clinical manifestations. Interventions such as image-guided aspiration or surgical procedures are appropriate when conservative measures prove ineffective.